A Survey of a Small Sample of Emergency Department and Admitted Patients Asking Whether They Expect to Be Tested for HIV Routinely. (July 2013) - McAfee, Lisa; Tung, Chester; Espinosa-Silva, Yaminah; Rahman, Munira; Fatima, Khuteja; Clark, Ryan; Wang, Zhijun; Pearce, Daniel
Objectives: Many US HIV-positive patients are unaware of their infection. Although there are multiple studies assessing the acceptance of testing, there are none that assess the patient's expectations of routine HIV testing. Methods: Through a prospective, cross-sectional, unfunded, convenience sample survey, we assessed the patient's expectation of testing at a regional medical center serving an indigent population. Also, we compared the providers' predictions of the proportion of patients expecting a test. Results: Of the 69 patients, 23% expected a test. The only factor that correlated with this was their desire to be tested ( P = .004). Providers' (N = 59) mean prediction was that 21% of the patients expected a test (range: 0%-100%). The proportion of emergency department (ED) patients wanting a test was 52% (of 30) and internal medicine inpatients were 44% (of 39). Conclusions: Nearly a quarter of patients expected routine HIV testing. This finding should encourage a review of policies promoting HIV testing, especially within the ED.